Evaluasi Implementasi Corporate Social Responsibilityuntuk Meningkatkan Kesejahteraan Masyarakat Dalam Bidang Pertanian - Lilik Indrawati; Setiadi Alim Lim (Fakultas Ekonomi Universitas Katolik Darma Cendika, 2015)
This research aims to assess the effectiveness of the implementation of corporate social responsibility program of longan planting done by the farmers in Galengloh Village, Pacet Subdistrict, Mojokerto District, East Java Province. This corporate social responsibility program is intended to increase the income of the local community. The results showed that the corporate social responsibility program that is implemented having some problems, among others, not all communities have the land to grow crops longan, not all farmers have a strong interest in developing a plant longan, lack of guidance/counseling on how to plant and maintain good longan and there is no clear picture longan marketing at harvest. If there is not a good treatment for these constraints, possibly the goal of corporate social responsibility program to increase the income of the people will not be reached. This research also found several problems encountered by society that can be used as another corporate social responsibility program.